Blending projects serving public education into teacher training - Turcsányi-Szabó, Márta (2006)
About 10 years ago informatics teacher training did not seem to be too productive. Even though many students graduated, most of them chose well paid jobs as IT specialists rather than underpaid teacher positions in Hungary. What is then the reason for striving to provide the most up-to-date technology and methodology for future teachers who will never be able to transfer their gained knowledge into public education? The only possible solution seemed to be to convert to e-learning. The significance of TeaM elearning activities at ELTE University is mainly that they are interconnected and add up from course project works, undergraduate diploma works, Ph.D. dissertations of students, as well as all local and international projects that TeaM Lab participates in. Thus a dynamic development is under continuous progress which is a win-win relationship between all participants, teacher training and projects.